Suicide Risk Assessment and Risk Formulation Part II: Suicide Risk Formulation and the Determination of Levels of Risk. Issue 4 (29th November 2013) - Berman, Alan L.; Silverman, Morton M.
<x xml:space="preserve">Abstract</x> The suicide risk formulation (SRF) is dependent on the data gathered in the suicide risk assessment. The SRF assigns a level of suicide risk that is intended to inform decisions about triage, treatment, management, and preventive interventions. However, there is little published about how to stratify and formulate suicide risk, what are the criteria for assigning levels of risk, and how triage and treatment decisions are correlated with levels of risk. The salient clinical issues that define an SRF are reviewed and modeling is suggested for an SRF that might guide clinical researchers toward the refinement of an SRF process.